Perlindungan Hukum Terhadap Korban Kekerasan Seksual Ditinjau Berdasarkan Undang - Undang Nomor 12 Tahun 2022 - Tristadewi, Refina (DOKTRINA: JOURNAL OF LAW, 2024)
Sexual violence is an unwanted act by someone against themselves that leads to sexuality. Victims of sexual violence are mostly minors, especially women. Victims of sexual violence are entitled to protection as stipulated in Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence. Which has the aim of preventing and dealing with sexual violence. The purpose of the research is to find out how legal protection for victims of sexual violence is reviewed based on the TPKS Law. This research uses normative research methods by examining secondary data sourced from literature and legal materials such as books, research journals, and legislation. The results showed that acts of sexual violence continue to occur in social life both committed by minors and adults. From January to 27 September 2023 there have been 19 thousand cases that have occurred. Therefore, the TPKS Law provides legal remedies in the form of protection for the rights of victims and also regulates criminal sanctions for perpetrators of sexual crimes.